2016
DOI: 10.11646/zootaxa.4150.4.4
|View full text |Cite|
|
Sign up to set email alerts
|

Checklist and analysis of completeness of the reef fish fauna of the Revillagigedo Archipelago, Mexico

Abstract: This paper presents an updated checklist of cartilaginous and bony fishes from the Revillagigedo Archipelago reefs and nearby areas (Tropical Eastern Pacific). To compile this list, we gathered data from field surveys between 1994 and 2015, from an exhaustive literature review, and by consulting museum collections and databases. With these records we estimated the completeness of the local fish inventory using four non-parametric rarefaction methods. We report a total of 389 species in 102 families; 235 of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
0
8
0
3
Order By: Relevance
“…To date, studies of the fish fauna in both areas have been oriented toward the specific analysis of particular aspects, mainly related to taxonomic listings and observations of the behavior and distribution of sharks and mantas, in the case of the Revillagigedo Archipelago (Castro‐Aguirre & Balart, ; Fourriére, et al, ; Del Moral‐Flores, Gracián‐Negrete, & Guzmán‐Camacho, ; Rubin et al, ). In Clipperton atoll, an analysis of the relationship between coral cover and depth was recently conducted (Ricart et al, ) and a checklist and study of the comprehensiveness of the fauna also exist (Fourriére et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, studies of the fish fauna in both areas have been oriented toward the specific analysis of particular aspects, mainly related to taxonomic listings and observations of the behavior and distribution of sharks and mantas, in the case of the Revillagigedo Archipelago (Castro‐Aguirre & Balart, ; Fourriére, et al, ; Del Moral‐Flores, Gracián‐Negrete, & Guzmán‐Camacho, ; Rubin et al, ). In Clipperton atoll, an analysis of the relationship between coral cover and depth was recently conducted (Ricart et al, ) and a checklist and study of the comprehensiveness of the fauna also exist (Fourriére et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still large areas and different environments in the ETP that must be systematically surveyed to obtain complete biological inventories. Our work and other similar studies [6365] have found gaps in the biological information for gobies in northwestern Mexico (Sinaloan Gap, Marias archipelago, Marietas and Isabel Island), the Revillagigedo archipelago, Central America and Colombia that need to be more adequately sampled.…”
Section: Discussionmentioning
confidence: 47%
“…According to governmental data, the archipelago presents an area of ecological richness comprising 35 species of sharks, 13 batoids and one holocephan (DOF, 2018). However, most of the original studies used for this estimation and other checklists of fishes are based on the potential distribution of several species with no evidence of occurrence in Revillagigedo reported to date (Bautista‐Romero et al ., 1994; Castañeda‐Beltrán, 1988; Castro‐Aguirre & Balart, 2002; Del Moral‐Flores et al ., 2016; Fourriére et al ., 2016; Miller & Lea, 1976). This likely constitutes an overestimation of the chondrichthyans that occur in the archipelago, which could lead to deficiencies in research and management direction efforts (Lester et al ., 2009; Cisneros‐Montemayor et al ., 2020).…”
Section: Figurementioning
confidence: 99%
“…DD, data deficient; NE, not listed; VU, vulnerable; LC, least concern; NT, near threatened; EN, endangered; CR, critically endangered. References: (1) Present paper; (2) Meléndez & Villavicencio‐Garayazar (1998); (3) Fourriére et al ., 2016; (4) Del Moral‐Flores et al . (2016); (5) Lara‐Lizardi et al .…”
Section: Figurementioning
confidence: 99%